Variationsrechnung: 20.6. bis 26.6.1976 - Heinz, Erhard; Hildebrandt, Stefan; Jäger, Willi (Tagungsbericht, 1976)
H.-W. Alt, Heidelberg; W. Alt, Heidelberg; J. Bemelmans, Bonn; R. Böhme, Erlangen; R. Bulirsch, München; G. Dziuk, Aachen; R. Finn, Stanford; J. Frehse, Bonn; C. Gerhardt, Heidelberg; E. Gonzalez, Povo; K. Gornik, Bonn; M. Grüter, Bonn; R. D. Gulliver, Bonn; A. van Harten, Amsterdam, F. P. Harth, Koblenz; E. Heinz, Göttingen; S. Hildebrandt, Bonn; E. Hölder, Mainz; W. Jäger, Heidelberg; H. Kaul, Bonn; H. Kielhöfer, Stuttgart; R. Landes, Bochum; F. Lewerenz, Göttingen; W. Littman, Minneapolis; St. Luckhaus, Heidelberg; M. Meier, Bonn; M. Miranda, Trento; J. S. Mitteau, Toulouse; D. Müller, Göttingen; J. C. C. Nitsche, Minneapolis; H. Pecher, Göttingen; H. Ruchert, Saarbrücken; Chr. G. Simader, München; L. Simon, Stanford; E. Sperner jun. , Bochum; K. Steffen, Düsseldorf; E. Tausch, Bonn; F. Tomi, Saarbrücken; A. J. Tromba, Santa Cruz; W. Velte, Würzburg; W. von Wahl, Bochum; M. Wiegner, Bochum; B. Winzell, Linköping